Aqueous zinc ion battery electrolyte and aqueous zinc ion battery

By using sodium dehydroacetate in the electrolyte of aqueous zinc ion battery, the problems of dendrites, corrosion and by-product aggregation on the zinc electrode are solved, and the cycle stability and life of the battery are improved.

CN119833782APending Publication Date: 2025-04-15HUNAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510024120.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The weak hydrogen bond network constructed by free water and solvated water in the electrolyte of existing aqueous zinc ion battery leads to harmful zinc dendrites on zinc electrodes, spontaneous corrosion and by-product aggregation, limiting the cycle stability and life of the battery.

Method used

By using sodium dehydroacetate as an additive in the electrolyte of aqueous zinc ion battery, the hydrogen bond network of free water in the electrolyte is broken, the water activity is reduced, and the hydrogen evolution reaction, corrosion side reaction and dendrites are inhibited.

Benefits of technology

Significantly reduce the corrosion and by-product generation of zinc metal anode surface, improve the electrochemical stability and cycle life of zinc anode, and enhance the specific capacity and Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833782A_ABST
    Figure CN119833782A_ABST
Patent Text Reader

Abstract

According to the aqueous zinc ion battery electrolyte and the aqueous zinc ion battery, sodium dehydroacetate is adopted as an electrolyte additive, the ionic conductivity of the electrolyte can be improved in the electrolyte, zinc ions are induced to be uniformly deposited, free water and structural water in the electrolyte are combined, a hydrogen bond network is broken, and the water activity is reduced; according to the water-based zinc ion battery, the Groterworth diffusion process of H < + > is hindered, so that hydrogen evolution reaction, corrosion side reaction and dendritic crystal growth are inhibited, the rate capability and the cycle performance of the water-based zinc ion battery are improved, and the problems that harmful zinc dendritic crystals, spontaneous corrosion, byproduct aggregation and the like on a zinc electrode are easily caused by high activity of water molecules of the existing water-based zinc ion battery are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aqueous zinc ion batteries, and more specifically, relates to an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery. Background Art

[0002] Lithium-ion batteries are widely used in electronic consumer products, electric vehicles, and grid energy storage due to their high energy and power density and long cycle life. However, the scarcity and high price of lithium resources and the safety issues of organic electrolytes limit their sustainable development. Among various aqueous metal-ion batteries, rechargeable aqueous zinc-ion batteries have broad application prospects in large-scale and distributed energy storage due to their abundant zinc resources, low cost, high safety, high specific capacity of zinc metal negative electrodes and low electrochemical potential.

[0003] However, zinc metal anodes still face some serious inherent problems in electrolytes. During battery cycling, dendrites continue to grow on the surface of zinc anodes, which may eventually pierce the separator and cause short circuits or sudden capacity drops. They also trigger other surface-related side reactions, such as corrosion and hydrogen evolution reaction (HER). This can significantly reduce the coulombic efficiency (CE) and cycle stability of the battery and hinder the practical application of zinc-ion batteries.

[0004] Electrolyte additives can significantly improve battery performance without increasing production costs or changing production processes. However, most additives are currently used in large quantities, resulting in a decrease in the intrinsic conductivity of aqueous electrolytes. Therefore, it is of great significance to find suitable additives to optimize zinc-ion battery electrolytes, regulate zinc ion transport at the negative electrode / electrolyte interface, inhibit zinc dendrites, hydrogen evolution and corrosion, and thereby improve the electrochemical stability and cycle life of the zinc negative electrode.

[0005] In CN117832652A, an aqueous zinc ion battery electrolyte additive, an electrolyte and an aqueous zinc ion battery are disclosed that the electrolyte additive is a water-soluble fluoroamino acid. The additive can change the Zn 2+ The carboxyl group will partially replace Zn 2+ The water molecules in the solvation shell reduce the water molecule content in the zinc complex, thereby inhibiting the hydrogen evolution reaction, the occurrence of corrosion passivation and the formation of the by-product basic zinc sulfate. On the other hand, under high current density, the additive can be adsorbed on the surface of the zinc negative electrode and form a layer of ZnF2 inorganic layer on the surface of the zinc negative electrode during the cycle, which can reduce the local current density on the surface of the zinc negative electrode and regulate the Zn 2+The additive can generate a fluorine-rich CEI film in situ on the surface of the positive electrode material during the battery charge and discharge cycle, effectively stabilize the structure of the positive electrode material, and inhibit the collapse of the positive electrode material structure and the dissolution of transition metal ions in the positive electrode material. However, the patent is powerless against the weak hydrogen bond network constructed by free water and solvated water in the electrolyte. It is these large amounts of free water with weak hydrogen bonds, the abundant bound water in the solvated structure of zinc ions, and the adsorbed water on the zinc electrode interface that together lead to the high activity of water molecules, causing persistent and deep-rooted problems such as harmful zinc dendrites, spontaneous corrosion, and by-product aggregation on the zinc electrode, posing a major threat to the further development of aqueous zinc-ion batteries. Summary of the invention

[0006] The present invention provides an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery to overcome the problems of harmful zinc dendrites on the zinc electrode, spontaneous corrosion and by-product aggregation caused by the weak hydrogen bond network constructed by free water and solvated water in the existing aqueous zinc ion battery electrolyte.

[0007] The present invention is achieved through the following technical solutions:

[0008] The invention discloses an aqueous zinc ion battery electrolyte, wherein the raw materials include soluble zinc salt, sodium dehydroacetate and water, wherein the concentration of the sodium dehydroacetate is 2mM to 18mM.

[0009] Furthermore, the soluble zinc salt includes one or more of zinc sulfate, zinc nitrate, zinc chloride and zinc trifluoromethanesulfonate.

[0010] Furthermore, the concentration of the soluble zinc salt is 1 to 3 mol / L.

[0011] Furthermore, the concentration of soluble zinc salt in the aqueous zinc ion battery electrolyte is 2.2 mol / L, and the concentration of sodium dehydroacetate is 4 mM.

[0012] Furthermore, the preparation step of the aqueous zinc ion battery electrolyte includes: dissolving a soluble zinc salt in deionized water to prepare a zinc salt solution, dissolving sodium dehydroacetate in deionized water to prepare a sodium dehydroacetate solution, and then adding the sodium dehydroacetate solution to the zinc salt solution, stirring, and preparing an electrolyte.

[0013] Furthermore, the stirring speed is 600-1400 r / min, and the stirring time is 5-10 min.

[0014] An aqueous zinc ion battery comprises the aqueous zinc ion battery electrolyte.

[0015] Furthermore, the aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte.

[0016] Furthermore, the positive electrode is vanadium pentoxide, vanadium dioxide or manganese dioxide, the negative electrode is a zinc sheet, and the separator is glass fiber.

[0017] Furthermore, the aqueous zinc ion battery includes one of an aqueous zinc ion symmetrical battery, an aqueous zinc ion zinc-copper battery, an aqueous zinc ion zinc stainless steel mesh battery and an aqueous zinc ion full battery.

[0018] Compared with the prior art, the beneficial effects are:

[0019] The present invention uses sodium dehydroacetate as an additive for an aqueous zinc ion battery electrolyte. In the process of zinc deposition, sodium dehydroacetate can provide a strong nucleation driving force and provide multiple nucleation sites, which are more conducive to the uniform deposition of zinc ions. Sodium dehydroacetate plays a role in refining grains and regulating the uniform deposition of zinc ions, thereby alleviating the hydrogen evolution corrosion reaction of the zinc metal anode, and can significantly reduce the corrosion on the surface of the zinc metal anode and the generation of by-products.

[0020] The present invention uses sodium dehydroacetate as an additive in the aqueous zinc ion battery electrolyte to improve the wettability of the zinc anode surface and optimize the Zn 2+ The dehydroacetate ion acts as a hydrogen bond acceptor, breaking the hydrogen bond network of free water in the electrolyte, reducing water activity, and hindering H + The Grotworth diffusion process can be inhibited, thereby inhibiting the hydrogen evolution reaction, corrosion side reaction and dendrite growth, reducing impedance, promoting the charge transfer dynamics at the electrode / electrolyte interface, and improving the specific capacity and cycle stability of aqueous zinc-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the FT-IR test curve diagram of Examples 1 to 3 and the comparative example, Figure 1 a is 4000~400cm -1 Fourier transform infrared spectrum, intercepting 3800~2800cm -1 do Figure 1 b, intercept 2400~1200cm -1 do Figure 1 c, intercept 1500~750cm -1 do Figure 1 d;

[0022] Figure 2 Linear scanning cyclic voltammetry (LSV) diagrams using the electrolytes of Examples 1 to 3 and the comparative example;

[0023] Figure 3 The Tafel curves are shown in Figure 2 and Figure 3 using the electrolytes of Example 2 and Comparative Example;

[0024] Figure 4 CV curves of zinc-copper half-cells in application examples 1 to 3 and comparative application examples;

[0025] Figure 5 For the zinc-copper batteries in application examples 1 to 3 and comparative application examples, after standing for 1 hour, the -2 Deposition overpotential diagram under current density;

[0026] Figure 6 At 5 mA cm -2 ,5mAh cm -2 Under the conditions, the metallographic microscope images of the Zn electrodeposition process in Examples 1 to 3 and the comparative example, wherein Figure 6 a is a comparative application example. Figure 6 b is application example 1, Figure 6 c is application example 2, Figure 6 d is application example 3;

[0027] Figure 7 The symmetrical battery in Application Examples 1 to 3 and Comparative Application Example at a current density of 5 mA cm -2 , with an area capacity of 1 mAh cm -2 Long cycle graph of ;

[0028] Figure 8 The symmetrical battery in Application Example 2 and Comparative Application Example at 1 mA cm -2 ,1mAh cm -2 SEM image of the battery cycled for 500 h at a current density of Figure 8 ad is a comparative application example. Figure 8 eh is application 2.

[0029] Fig. 9 The area capacity of the symmetrical battery in Application Example 2 and Comparative Application Example at different current densities is 1 mAh cm -2 The rate performance comparison chart shows Fig. 9 a is a comparison chart of the rate performance from 0 to 90 hours, and the rate performance from 17 to 30 hours is shown as Fig. 9 b;

[0030] Fig.10 The zinc-copper battery in Application Example 2 and Comparative Application Example has a current density of 1 mA cm -2 , area capacity is 1 mAhcm -2 Coulomb efficiency diagram;

[0031] Fig.11 The full battery in Application Example 2 and Comparative Application Example is at a current density of 1A g -1 Rate performance diagram

[0032] Fig.12The full battery in Application Example 2 and Comparative Application Example is at a current density of 1A g -1 Long cycle diagram. DETAILED DESCRIPTION

[0033] The following is further explained and illustrated in conjunction with the examples, but the specific examples do not limit the present invention in any form. Unless otherwise specified, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are conventional commercially available raw materials.

[0034] Example 1

[0035] An aqueous zinc ion battery electrolyte containing an additive, comprising zinc sulfate, water and an additive; the additive is sodium dehydroacetate; the concentration of the zinc sulfate is 2.2 mol / L;

[0036] The preparation method of the aqueous zinc ion battery electrolyte containing the additive comprises the following specific steps:

[0037] (1) 9.4895 g of zinc sulfate heptahydrate was dispersed in 11.22 mL of deionized water, and the solution was fixed to 15 mL, which was then magnetically stirred at room temperature until the zinc sulfate was completely dissolved, thereby obtaining a 2.2 M ZnSO4 electrolyte.

[0038] (2) Disperse 0.4182 g of sodium dehydroacetate in 5 mL of deionized water, stir the mixture magnetically at room temperature until the sodium dehydroacetate is completely dissolved, and filter the mixture once to obtain a 0.4 M sodium dehydroacetate solution.

[0039] (3) The sodium dehydroacetate solution is transferred into the zinc sulfate solution to form a uniform suspension in which the volume fraction of the sodium dehydroacetate solution in the electrolyte is 0.5%, and the mixture is stirred thoroughly to obtain an electrolyte.

[0040] Example 2

[0041] An aqueous zinc ion battery electrolyte containing an additive, comprising zinc sulfate, water and an additive; the additive is sodium dehydroacetate; the concentration of the zinc sulfate is 2.2 mol / L;

[0042] The preparation method of the aqueous zinc ion battery electrolyte containing the additive comprises the following specific steps:

[0043] (1) 9.4895 g of zinc sulfate heptahydrate was dispersed in 11.22 mL of deionized water, and the solution was fixed to 15 mL, which was then magnetically stirred at room temperature until the zinc sulfate was completely dissolved, thereby obtaining a 2.2 M ZnSO4 electrolyte.

[0044] (2) Disperse 0.4182 g of sodium dehydroacetate in 5 mL of deionized water, stir the mixture magnetically at room temperature until the sodium dehydroacetate is completely dissolved, and filter the mixture once to obtain a 0.4 M sodium dehydroacetate solution.

[0045] (3) The sodium dehydroacetate solution is transferred into the zinc sulfate solution to form a uniform suspension in which the volume fraction of the sodium dehydroacetate solution in the electrolyte is 1%, and the mixture is stirred thoroughly to obtain an electrolyte.

[0046] Example 3

[0047] An aqueous zinc ion battery electrolyte containing an additive, comprising zinc sulfate, water and an additive; the additive is sodium dehydroacetate; the concentration of the zinc sulfate is 2.2 mol / L;

[0048] The preparation method of the aqueous zinc ion battery electrolyte containing the additive comprises the following specific steps:

[0049] (1) 9.4895 g of zinc sulfate heptahydrate was dispersed in 11.22 mL of deionized water, and the solution was fixed to 15 mL, which was then magnetically stirred at room temperature until the zinc sulfate was completely dissolved, thereby obtaining a 2.2 M ZnSO4 electrolyte.

[0050] (2) Disperse 0.4182 g of sodium dehydroacetate in 5 mL of deionized water, stir the mixture magnetically at room temperature until the sodium dehydroacetate is completely dissolved, and filter the mixture once to obtain a 0.4 M sodium dehydroacetate solution.

[0051] (3) The sodium dehydroacetate solution is transferred into the zinc sulfate solution to form a uniform suspension in which the volume fraction of the sodium dehydroacetate solution in the electrolyte is 2%, and the mixture is stirred thoroughly to obtain an electrolyte.

[0052] Comparative Example 1

[0053] An aqueous zinc ion battery electrolyte, comprising zinc sulfate and water; the concentration of the zinc sulfate is 2.2 mol / L;

[0054] The preparation method of the aqueous zinc ion battery electrolyte comprises the following specific steps: dispersing 9.4895 g of zinc sulfate heptahydrate in 11.22 mL of deionized water, making a 15 mL solution by fixed volume, and then magnetically stirring the solution at room temperature until the zinc sulfate is completely dissolved to obtain a 2.2 M ZnSO4 electrolyte.

[0055] The soluble zinc salt in the above embodiment can also be selected from one of zinc nitrate, zinc chloride and zinc trifluoromethanesulfonate.

[0056] like Figure 1 As shown in the example, water reacts with the carbonyl group (-C=O) and the negatively charged hydroxyl oxygen (-O- ) hydrogen bonds with the OH stretching vibration of water ( Figure 1 b) Peak blue shift, bending vibration ( Figure 1 c) The peak is red-shifted. Hydrogen bonds are formed between sodium dehydroacetate and water, changing the vibration mode of water molecules. 2- The peak positions showed different degrees of blue shift compared with the control samples ( Figure 1 d), that is, the introduction of sodium dehydroacetate can adjust the Zn 2+ The solvation sheath of Zn 2+ and SO4 2- The electrostatic coupling between them and the established hydrogen bond network help to lock the migration of water molecules and limit their decomposition.

[0057] like Figure 2 As shown, from the perspective of hydrogen evolution potential, when the sodium dehydroacetate additive is present, the hydrogen evolution reaction is inhibited, and when the volume fraction of the additive is 1%, the hydrogen evolution reaction is inhibited to the greatest extent.

[0058] like Figure 3 As shown, the corrosion potential of the zinc negative electrode in the comparative example is -0.984V (vs. Ag / AgCl), while the corrosion potential of the metal zinc in Example 2 increases to -0.975V (vs. Ag / AgCl). The increase in corrosion potential indicates that Example 2 reduces the possibility of corrosion side reactions at the zinc negative electrode / electrolyte interface. The probability of corrosion reactions at the zinc negative electrode / electrolyte interface is reduced and the rate is slowed down, which is beneficial to improve the reversibility of zinc deposition / dissolution on the zinc negative electrode and increase the cycle life of the battery.

[0059] Application Example 1

[0060] Preparation of aqueous zinc ion symmetric battery: 150 μL of the modified electrolyte prepared in Example 1 was dropped on the glass fiber, and the symmetric battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode zinc sheet-gasket-positive electrode shell.

[0061] Preparation of aqueous zinc ion zinc-copper battery: 150 μL of the modified electrolyte prepared in Example 1 was dropped on the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode copper sheet-gasket-positive electrode shell.

[0062] Preparation of aqueous zinc ion full battery: 150 μL of the modified electrolyte prepared in Example 1 was dropped on the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode stainless steel mesh loaded with VO2-gasket-positive electrode shell.

[0063] Application Example 2

[0064] Preparation of aqueous zinc ion symmetric battery: 150 μL of the modified electrolyte prepared in Example 2 was dropped on the glass fiber, and the symmetric battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode zinc sheet-gasket-positive electrode shell.

[0065] Preparation of aqueous zinc ion zinc-copper battery: 150 μL of the modified electrolyte prepared in Example 2 was dropped on the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode copper sheet-gasket-positive electrode shell.

[0066] Preparation of aqueous zinc ion full battery: 150 μL of the modified electrolyte prepared in Example 2 was dropped on the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode stainless steel mesh loaded with VO2-gasket-positive electrode shell.

[0067] Application Example 3

[0068] Preparation of aqueous zinc ion symmetric battery: 150 μL of the modified electrolyte prepared in Example 3 was dropped on the glass fiber, and the symmetric battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode zinc sheet-gasket-positive electrode shell.

[0069] Preparation of aqueous zinc ion zinc-copper battery: 150 μL of the modified electrolyte prepared in Example 3 was dropped on the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode copper sheet-gasket-positive electrode shell.

[0070] Preparation of aqueous zinc ion full battery: 150 μL of the modified electrolyte prepared in Example 3 was dropped on the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode stainless steel mesh loaded with VO2-gasket-positive electrode shell.

[0071] Comparative Application Examples

[0072] Preparation of aqueous zinc ion symmetrical battery: 150 μL of the modified electrolyte prepared in the comparative example was dropped on the glass fiber, and the symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode zinc sheet-gasket-positive electrode shell.

[0073] Preparation of aqueous zinc ion zinc-copper battery: 150 μL of the modified electrolyte prepared in the comparative example was dropped onto the glass fiber, and a symmetrical battery was assembled in the order of negative electrode shell-negative electrode zinc sheet-diaphragm-electrolyte-positive electrode copper sheet-gasket-positive electrode shell.

[0074] Preparation of aqueous zinc ion full battery: drop 150 μL of the modified electrolyte prepared in the comparative example on the glass fiber, and assemble a symmetrical battery in the order of negative electrode shell - negative electrode zinc sheet - diaphragm - electrolyte - positive electrode stainless steel mesh loaded with VO2 - gasket - positive electrode shell.

[0075] from Figure 4 It can be seen that the large nucleation overpotential (NOP) of application example 2 (102mV) increases by 55mV compared with the comparative application example. According to the minimum Gibb free energy and classical nucleation theory, the high NOP gives a strong nucleation driving force and smaller nucleation grains, providing more nucleation sites, which is conducive to uniform and dense Zn deposition.

[0076] from Figure 5 It can be seen that Application Example 2 exhibits a deposition overpotential of 122.5 mV, which is much higher than the deposition overpotential of 58.9 mV in the comparative application example. This indicates that after the introduction of sodium dehydroacetate, the nucleation barrier of Zn becomes higher, which inhibits the growth of dendrites to a certain extent, improves the stability of the zinc metal negative electrode, and is conducive to extending the cycle life of the battery.

[0077] from Figure 6 It can be seen intuitively that the particles on the surface of the zinc sheet after the Zn electrodeposition process in the examples are finer than the particles on the surface of the zinc sheet after the Zn electrodeposition process in the comparative examples, among which Example 2 is the most obvious.

[0078] from Figure 7 It can be seen that in the comparative application example, the cycle life of the symmetrical battery with blank electrolyte does not exceed 100h, while the cycle life of the symmetrical battery with 0.5% sodium dehydroacetate electrolyte added by volume in Application Example 1 exceeds 750h, the cycle life of the symmetrical battery with 2% sodium dehydroacetate electrolyte added by volume in Application Example 3 exceeds 1000h, and the cycle life of the symmetrical battery with 1% sodium dehydroacetate electrolyte added by volume in Application Example 2 exceeds 2000h.

[0079] from Figure 8 It can be seen from the comparative application example that at 1mA cm -2 ,1mAh cm -2 Dendrites will form at a current density of Figure 8 a. Figure 8 b); After 500 h of cycling, the dendrites pierced the glass fiber membrane ( Figure 8 c), and irregular dendrite stacks are formed on the surface of the zinc metal negative electrode, resulting in a short circuit in the symmetrical battery. However, after cycling under this condition, the high nucleation overpotential (NOP) of Application Example 2 gives a strong nucleation driving force and smaller nucleation grains, forming a dense deposition structure on the surface of the zinc metal negative electrode of Application Example 2.

[0080] from Fig. 9As can be seen from a, the symmetrical battery in Application Example 2 has a current density of 1-5 mA cm -2 ,1mAh cm -2 The deposition and removal of zinc ions can be ensured at a current density of 1 mA cm -2 ,1mAh cm -2 To 2mA cm -2 ,1mAh cm -2 Soft short circuit occurs when changing Fig. 9 b).

[0081] from Fig.10 It can be seen that the zinc-copper battery with blank electrolyte in the comparative application example failed after more than 100 cycles, while the zinc-copper battery with electrolyte with a volume fraction of 1% dehydroacetic acid sodium added in application example 2 lasted for more than 1000 cycles.

[0082] from Fig.11 It can be seen that the full battery rate capacity of the electrolyte in the comparative application example is lower than the full battery capacity of the electrolyte in application example 2 to which sodium dehydroacetate is added.

[0083] from Fig.12 It can be seen that the full battery long cycle capacity of the electrolyte in the comparative application example is lower than the full battery capacity of the electrolyte in application example 2 to which sodium dehydroacetate is added.

[0084] The Zn-ion battery prepared by using ZnSO4 electrolyte with sodium dehydroacetate additive at 5 mA cm -2 、1mAh cm -2 The cycle performance at a current density of 2000 h reaches 2000 h, and the CE value in the full battery is stable and close to 100%, which is much better than that of ZnSO4 electrolyte. Therefore, the use of sodium dehydroacetate additives has achieved highly stable and long cycle life aqueous zinc ion batteries. The present invention provides a strategy for solving the problems of dendrite formation, corrosion and side reactions, and promotes the development of next-generation high-performance ZIBs.

[0085] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An aqueous zinc ion battery electrolyte, characterized in that The raw materials include soluble zinc salt, sodium dehydroacetate and water, wherein the concentration of the sodium dehydroacetate is 2mM to 18mM.

2. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The soluble zinc salt includes one or more of zinc sulfate, zinc nitrate, zinc chloride and zinc trifluoromethanesulfonate.

3. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of the soluble zinc salt is 1-3 mol / L.

4. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of soluble zinc salt in the aqueous zinc ion battery electrolyte is 2.2 mol / L, and the concentration of sodium dehydroacetate is 4 mM.

5. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The preparation steps of the aqueous zinc ion battery electrolyte include: dissolving a soluble zinc salt in deionized water to prepare a zinc salt solution, dissolving sodium dehydroacetate in deionized water to prepare a sodium dehydroacetate solution, and then adding the sodium dehydroacetate solution to the zinc salt solution and stirring to prepare an electrolyte.

6. The aqueous zinc ion battery electrolyte according to claim 5, characterized in that: The stirring speed is 600-1400 r / min, and the stirring time is 5-10 min.

7. An aqueous zinc ion battery, characterized in that: The invention comprises the aqueous zinc ion battery electrolyte according to any one of claims 1 to 6.

8. The aqueous zinc ion battery according to claim 7, characterized in that: The aqueous zinc ion battery comprises a positive electrode, a negative electrode and an electrolyte.

9. The aqueous zinc ion battery according to claim 8, characterized in that: The positive electrode is vanadium pentoxide, vanadium dioxide or manganese dioxide, the negative electrode is a zinc sheet, and the separator is glass fiber.

10. The aqueous zinc ion battery according to claim 7, characterized in that: The aqueous zinc ion battery includes an aqueous zinc ion symmetrical battery, an aqueous zinc ion zinc-copper battery, an aqueous zinc ion zinc stainless steel mesh battery and an aqueous zinc ion full battery.

Citation Information

Patent Citations

  • Organic salt capable of inhibiting dendritic crystal, corrosion and other side reactions as aqueous zinc ion battery electrolyte

    CN114824511A